Accuracy and Reliability of Inertial Devices for Load Assessment During Flywheel Workout - Pino-Ortega, Jose (2021)
There is currently an increase in inertial flywheel application in strength training; thus, it must be monitored by an accurate and reliable device. The present study tested: (1) the accuracy of an inertial measurement device (IMU) to correctly measure angular velocity and (2) its inter-unit reliability for the measurement of external load. The analysis was performed using Pearson Correlation and Intraclass Correlation Coefficient (ICC). The IMU accuracy was tested using Bland-Altman and the reliability with the coefficient of variation (CV). Ten elite-level football players performed ten series of 5 repetitions in a one-hand standing row exercise (5 series with each arm). A nearly perfect accuracy (ICC=.999) and a very good between-device reliability (Bias=-.010; CV=.017%) was found. IMU is a reliable and valid device to assess angular velocity in inertial flywheel workout objectively.